2020
DOI: 10.21203/rs.2.14506/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide analysis of Myo-inositol oxygenase gene family in tomato reveals their involvement in ascorbic acid accumulation

Abstract: Background Ascorbic acid (Vitamin C, AsA) is an antioxidant metabolite involved in plant development and environmental stimuli. AsA biosynthesis has been well studied in plants, and MIOX is a critical enzyme in plants AsA biosynthesis pathway. However, Myo-inositol oxygenase (MIOX) gene family members and their involvement in AsA biosynthesis and response to abiotic stress remain unclear. Results In this study, five tomato genes encoding MIOX proteins and possessing MIOX motifs were identified. Structural an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…The thermal tolerance of organisms has been identified as a complex multi-genic trait that involves multiple physiological and biochemical mechanisms and requires the coordinated and precise activation of numerous genes (Sun et al 2021 ; Pudake et al 2017 ). However, previous studies on different species, including animals, plants and microorganisms, have shown that over-expressing a single HSP70 effectively improves thermal stability (D’Souza et al 2022 ; Ni et al 2021 ; Montero-Barrientos et al 2010 ). In our study, transgenic Tv-1511 strains over-expressing TvHSP70 exhibited significant growth advantages and maintained an improved growth-promoting ability compared with WT strains under heat stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermal tolerance of organisms has been identified as a complex multi-genic trait that involves multiple physiological and biochemical mechanisms and requires the coordinated and precise activation of numerous genes (Sun et al 2021 ; Pudake et al 2017 ). However, previous studies on different species, including animals, plants and microorganisms, have shown that over-expressing a single HSP70 effectively improves thermal stability (D’Souza et al 2022 ; Ni et al 2021 ; Montero-Barrientos et al 2010 ). In our study, transgenic Tv-1511 strains over-expressing TvHSP70 exhibited significant growth advantages and maintained an improved growth-promoting ability compared with WT strains under heat stress.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several genes involved in glutathione (Yamazaki et al 2019 ), carotenoid (Yu and Tian. 2021 ), ascorbate (Munir et al 2020 ), unsaturated fatty acid biosynthesis (Xue et al 2020 ) and phenylalanine metabolism (Xu and Zhang. 2020 ) were significantly activated in the transgenic strains.…”
Section: Discussionmentioning
confidence: 99%
“…No gene was found at the first SNP on the second chromosome, but this SNP was upstream to AT2G19800, a gene that encodes a myo-inositol oxygenase (MIOX). MIOX gene family is involved in oxidative stress tolerance (Munir et al, 2020). On the fourth chromosome, a significant SNP was located in AT4G27080, a gene that encodes a disulphide isomerase-like (PDIL) protein (Table S1), involved in biotic and abiotic stress tolerance (Chen et al, 2012;Wang et al, 2019).…”
Section: Genotypic and Allelic Effects Of Attractivity Of Plants Expo...mentioning
confidence: 99%
“…Возможное объяснение в дополнение к сформулированному выше предположению, что транскрипционная активность гена GME1 может влиять на содержание аскорбата в плодах на стадиях, предшествующих полной зрелости, состоит в том, что GME1, помимо биосинтеза аскорбата, активно вовлечен в синтез клеточной стенки во время роста плода (38). Также следует учитывать, что помимо L-галактозного пути, для образования аскорбата в плодах томата могут быть использованы другие альтернативные пути биосинтеза, например мио-инозитольный (39).…”
Section: характеристика идентифицированных генов-гомологов Gme1 у изу...unclassified